The Effect of Age on Right Ventricular Diastolic Function in Healthy Subjects Undergoing Treadmill Exercise Test. Issue 3 (5th July 2014) - Celik, Murat; Yalcinkaya, Emre; Yuksel, Uygar Cagdas; Gokoglan, Yalcin; Bugan, Baris; Kabul, Hasan Kutsi; Barcin, Cem
<x xml:space="preserve">Abstract</x> Objective There is an increasing interest for the value of right ventricle (RV) in predicting exercise tolerance and prognosis in cardiovascular disease. However, there is relatively few data evaluating the effect of age on RV diastolic filling velocities during rest or exercise in healthy subjects. Methods A total of 54 healthy subjects were enrolled in this study. Patients were divided into 2 groups according to their age: Group 1 (≤45‐years‐old) and Group 2 (>45‐years‐old). A treadmill exercise test was performed using modified Bruce protocol. Conventional pulsed‐wave Doppler and tissue Doppler velocities were obtained both at rest and immediately after the end of exercise, respectively. Results In the overall analysis, tricuspid flow Doppler analysis showed a significant increase in A‐wave velocity, less marked rise in E‐wave velocity, decreased E/A ratio and decreased E‐wave deceleration time (EDT) with exercise. Tissue Doppler analysis revealed increased Aa velocity, decreased in Ea/Aa ratio and IVRT. No significant change was observed in Ea velocity and E/Ea ratio with exercise. Although diastolic velocities changed significantly with exercise, systolic velocities did not. Cardiac response to exercise differed slightly in the older subjects compared to younger ones. The older subjects were more likely to have a reduced mean rate of RV filling for the second half of diastole from baseline to peak exercise. Conclusion To distinguish normal physiological changes due to aging from those of pathologic conditions may provide benefits while evaluating patients with known or suspected cardiovascular disease.